Sumber Daya Lembaga Dalam Praktek Dunia Pendidikan - Chelda Yuliana; Zaenab Hanim; Mochammad Samsul Huda; Muhammad Yamin (Journal on Education, 2023)
Education is a human effort to develop innate potentials, both physical and spiritual, so that they are in accordance with the values that exist in society and culture. Educational activities always take place in an environment called the educational environment. The educational environment is needed as an effective teaching process, because in the educational environment there are the infrastructure needed to achieve goals in education. It is not only the educational environment that plays a role, there are also educational institutions as managers. The development of increasingly advanced and developing science and technology makes educational institutions required to be able to improve their quality in facing the challenges and developments of the times. Education as a totality of efforts and actions must be carried out through three educational institutions namely, family, school and community. Therefore, it is necessary to integrate family education institutions, school education and community education institutions in carrying out character education. Strengthening the three educational institutions shows that character education is needed in order to anticipate increasingly complex problems in the future. The existence of educational institutions is the answer to the problems of human growth and development itself. Education that will form and foster forms with certain behaviors in certain circumstances, educational institutions require certain treatment as well. The role of these educational institutions varies, depending on the environment in which the institution is established, the family, school and community that are interconnected with one another.